KONSEP TAKHARUJ ALTERNATIF PEMBAGIAN WARISAN - Hamdani Hamdani (Sekolah Tinggi Ilmu Ekonomi Syariah Baktiya Aceh Utara, 2020)
ABSTRACT The system for distributing inheritance and the size of the share of each heir in Islam is certain as described by Allah SWT, in the Qur'an surah an-Nisa verses 11, 12, and 176 and the Hadith of the Prophet Muhammad, however, it does not close the way for deliberation. between the heirs to share the inheritance at the will of the heirs' willingness, namely by way of takharuj. This takharuj is justified to be taken by Islam as long as there are no parties who are harmed and on a willing basis. Takharuj is the result of deliberation carried out by all heirs to share inheritance kinship. In the implementation of the distribution of inheritance according to the heirs agree on the exit or resignation of one of the heirs or the heirs not to receive their share rights from the inheritance of the inheritor on condition that they receive a certain amount of money or goods from other heirs. This implementation of the jurists refers to the atsar of friends for the events that occurred during the reign of Caliph Usman bin Affan, where one of the wives of Abdurrahman bin 'Auf was invited to make peace by the heirs of the property amounting to eighty three thousand by removing it from the distribution of the inheritance. Therefore, the sharing of inheritance in takharuj by the heirs is justified by syara 'and it becomes an alternative in the distribution of inheritance by not following the provisions of Islamic inheritance.ABSTRAK ABSTRAK Sistem pembagian warisan dan besarnya bagian masing-masing ahli waris dalam Islam telah tertentu sebagaimana dijelaskan oleh Allah SWT, dalam al- Qur‟an surah an-Nisa ayat 11, 12, dan 176 dan Hadits Rasulullah SAW, namun demikian tidak menutup jalan dilakukan musyawarah antara ahli waris untuk membagi warisan atas kehendak kerelaan ahli waris, yaitu dengan jalan takharuj. Takharuj ini dibenarkan untuk ditempuh oleh Islam sepanjang tidak ada pihak-pihak yang dirugikan dan atas dasar kerelaan. Takharuj adalah hasil musyawarah yang dilakukan oleh semua ahli waris untuk membagi harta warisan secara kekeluargaan. Dalam pelaksanaan pembagian warisan secara takharuj para ahli waris bersepakat atas keluarnya atau mundurnya salah seorang ahli waris atau sebagaian ahli waris untuk tidak menerima hak bagiannya dari harta warisan peninggalan pewaris dengan syarat mendapat imbalan tertentu berupa sejumlah uang atau barang dari ahli waris lain. Pelaksanaan ini para fuqaha merujuk kepada atsar sahabat atas peristiwa yang terjadi pada masa pemerintahan Khalifah Usman bin Affan, dimana salah seorang istri Abdurrahman bin Auf diajak untuk berdamai oleh para ahli waris terhadap harta sejumlah delapan puluh tiga ribu dengan mengeluarkannya dari pembagian harta warisan. Oleh karena itu pembagian warisan secara takharuj oleh ahli waris dibenarkan oleh syara‟ dan ia menjadi suatu alternatif dalam pembagian warisan dengan tidak mengikuti ketentuan dalam kewarisan Islam. Kata Kunci: Al-Takharuj, Warisan, Alternatif